Intestinal Expression of miR-130b, miR-410b, and miR-98a in Experimental Canine Echinococcosis by Stem-Loop RT-qPCR - Faridi, Ashkan; Afgar, Ali; Mousavi, Seyed Mohammad; Nasibi, Saeid; Mohammadi, Mohammad Ali; Farajli Abbasi, Mohammad; Fasihi Harandi, Majid (Frontiers in Veterinary Science, 2020)
Echinococcus granulosus is a zoonotic cestode dwelling in the small intestine of canid definitive hosts. Intermediate hosts are a wide range of domestic and wild ungulates. Human infection with the larval stage causes cystic echinococcosis. Understanding the nature and extent of molecular mechanisms involved in host-parasite interactions helps to answer some very basic questions in the biology of cestode parasites with significant implications in the management and control of cystic echinococcosis. Little is known on the miRNAs expression in the intestinal tissues of dogs infected with E. granulosus. In the present study expression of a selected profile of miRNAs was evaluated in experimental canine echinococcosis. MiRNAs were extracted from 20 different parts of small intestinal tract of two sibling 3-month old mix-breed dogs. Complementary DNA was specifically synthesized using an optimized stem-loop system. Intestinal expression of four miRNAs (cfa-let7g, cfa-miR-98, cfamiR-410, cfa-miR-130b) was evaluated using RT-qPCR. The results of the study indicate a significant difference between test and control dogs in cfamiR-130b, cfa-miR-98, cfa-miR-410 (P≤0.05), however there was no significant difference for cfa-let7g. The most upregulated miRNAs were cfamiR-130b and cfa-miR-98. An increasing trend for cfa-let7g and a declining trend for cfa-miR-98, cfa-miR-410 and cfamiR-130b were found towards the distal segments of the small intestine. Our study revealed that cfa-miR-98, cfa-miR-410 and cfamiR-130b are involved in the definitive host response in canine echinococcosis. The study provides new information on the molecular basis of interactions between E. granulosus and dog in terms of miRNA expression and showed that E. granulosus infection could increase the expression of some pro-inflammatory miRNAs at the cellular level in the definitive host.